2013
DOI: 10.1371/journal.pgen.1003177
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of Pax6 Loci from the Elephant Shark Reveals a Family of Pax6 Genes in Vertebrate Genomes, Forged by Ancient Duplications and Divergences

Abstract: Pax6 is a developmental control gene essential for eye development throughout the animal kingdom. In addition, Pax6 plays key roles in other parts of the CNS, olfactory system, and pancreas. In mammals a single Pax6 gene encoding multiple isoforms delivers these pleiotropic functions. Here we provide evidence that the genomes of many other vertebrate species contain multiple Pax6 loci. We sequenced Pax6-containing BACs from the cartilaginous elephant shark (Callorhinchus milii) and found two distinct Pax6 loci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 93 publications
6
85
0
Order By: Relevance
“…In contrast to the downstream region of PAX6 , which has a significant role in disease aetiology of aniridia patients, the upstream region towards RCN1 is less well studied; it includes the only E-200 element and E-55 cluster, implicating this region as a regulatory ‘desert’ even though it is known to contain a number of evolutionarily conserved sites (23,24). As cis -regulatory elements are key to modulation of gene expression through transcription factor binding and are increasingly linked to complex disease phenotypes, we set out to identify and characterize novel PAX6 regulatory elements specific to pancreatic expression, owing to its roles in pancreatic development and T2D.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the downstream region of PAX6 , which has a significant role in disease aetiology of aniridia patients, the upstream region towards RCN1 is less well studied; it includes the only E-200 element and E-55 cluster, implicating this region as a regulatory ‘desert’ even though it is known to contain a number of evolutionarily conserved sites (23,24). As cis -regulatory elements are key to modulation of gene expression through transcription factor binding and are increasingly linked to complex disease phenotypes, we set out to identify and characterize novel PAX6 regulatory elements specific to pancreatic expression, owing to its roles in pancreatic development and T2D.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, there is another possibility that a second pax6 -related gene, pax6.2, may have redundant function in Xenopus embryos and may partially rescue pax6 mutations. It was recently discovered that non-mammalian vertebrates all appear to have this second pax6 -like gene and that the gene has been lost in birds and mammals (Ravi et al, 2013). X. tropicalis Pax6.2 (XM_004912020) consists of 281 amino acids and has 85% amino-acid identity with the region of amino acids 137–424 of X. tropicalis Pax6.…”
Section: Resultsmentioning
confidence: 99%
“…We have already used CRISPR-mediated gene targeting to mutate the pax6.2 and are currently raising animals to evaluate the contribution of this gene to eye development. It has been shown that in zebrafish, an antisense morpholino oligonucleotide directed against pax6.2 does reduce eye size in wild-type embryos (Ravi et al, 2013). Our analysis of expression of pax6.2 is consistent with a role in retinal phenotype in the pax6 mutant because, as noted earlier, expression is restricted to the dorsal retina (which persists in the mutant), but also we note that pax6.2 is not expressed in the lens, and that the lens is completely absent in the pax6 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The amplicon was cloned directly into an hsp68-LacZ vector containing a P4-P1r entry cassette [28]. Transgenic mice were generated by microinjection into mouse oocytes, and the analysis of transgenic lines was carried out as previously described [28]. Two independently derived E11.5 SBE6.1-LacZ embryos were independently analysed; one a transient insertion, the second from a stable line.…”
Section: Methodsmentioning
confidence: 99%